Deploying Blended Learning in the New Normal Pedagogy: Challenges and Prospects in Bangladesh - Mohammad Ehsanul Islam Khan (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2021)
While the world is experiencing a severe global crisis for the Covid-19 pandemic, the academic education sectors of several developing countries face formidable challenges, including Bangladesh. The current study aimed at finding out the barriers and possibilities for blended learning in the new normal situation in the education sector of Bangladesh. The researcher followed a descriptive approach with reviews of related literature and conducted Focus Group Discussions (FGD) with twenty-one university teachers to collect data and develop the study. The study found some challenges for blended education, e.g., poverty, lack of familial and institutional support, inadequate internet facilities, untrained teachers for using technological gadgets, electricity issues in rural and coastal areas. Still, the study found prospects to deploy blended learning and flipped classrooms in the post-pandemic period because of the countenance of 71.43% of participants. Finally, the study recommended some possible strategies in the new normal life for a more balanced educational system, particularly at the tertiary level.